A working life for people with severe mental illness - Becker, Deborah R. (Innovations in practice and service delivery with vulnerable populations., 2003)
Supported employment is a conceptual approach to vocational rehabilitation designed for people with developmental disabilities. The Individual Placement and Support (IPS) method described within utilizes the concept, but modifies it for the severely mentally ill.